Ineffective Breastfeeding Nursing Care for Post-Caesarean Section Mothers Using Oxytocin Massage Techniques at Dr. R Goeteng Taroenadibrata Regional General Hospital - Pungki, Diaz Vinalia; wirakhmi, Ikit Netra; Ma'rifah, Atun Roudotuk (Kirana Publisher (KNPub), 2025)
Ineffective breastfeeding is a common issue among post-cesarean mothers due to inadequate milk supply, postoperative pain, and psychological distress. This study aims to evaluate the effectiveness of oxytocin massage in improving breast milk production and release. A descriptive case study was conducted on a 27-year-old mother experiencing breastfeeding difficulties after cesarean delivery. Nursing interventions were provided over three consecutive days, including breastfeeding education, oxytocin massage, and emotional support. The results showed improved milk flow, reduced maternal anxiety, and better infant latch. Oxytocin massage proved to be an effective non-pharmacological intervention for addressing ineffective breastfeeding. This study recommends integrating oxytocin massage into postpartum nursing care.